CUSTOMS POLICY OF UKRAINE IN THE CONTEXT OF CYCLICAL ECONOMIC DEVELOPMENT - O.V. Kostiana; O. E. Naydenko; V. F. Tyschenko; V.M. Ostapenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2020)
It was determined that the Ukrainian economy is much more exposed to sharp fluctuations in economic activity, while the development of the economies of the EU countries is more stable and predictable without rapid jumps in economic development. The main factors influencing the cyclical development of the Ukrainian economy were analyzed in the article. The significant influence of the political situation on the economic development of Ukraine is determined. The substantive influence of foreign economic factors on the development of economic processes in Ukraine is substantiated. It is determined that effective and balanced customs policy of Ukraine can promote the rapid development of foreign trade, which will help to overcome the negative consequences of cyclical economic development. The creation of a free trade zone between Ukraine and EU countries in the context of cyclical economic development is considered. The main advantages and probable risks of reducing tariff and nontariff barriers in trade between Ukraine and the EU countries are revealed. Considered the volume of trade flows between Ukraine and the EU, it is substantiated that Ukraine has a rather weak position in trade relations with EU countries, this is reflected in the negative balance of foreign trade with the EU countries, as well as in the attraction of exports of goods with low value added. The volume of tax revenues for international trade to the State Budget of Ukraine is analyzed, on the basis of which it is determined that the liberalization of trade relations with the EU in the first periods of the creation of the free trade zone has led to a significant reduction of customs duties to the State Budget of Ukraine. It is substantiated that the establishment of a free trade zone with the EU would be less threatening in terms of the interests of the Ukrainian economy, in the event that it took place during the period of stable economic growth.